Analysis of Prospective Elementary School Teachers' Inquisitiveness in Solving Mathematics Problems - Hadi, Fida Rahmantika; Maharani, Swasti (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Teachers must model critical thinking skills and dispositions in front of their students. This is useful for helping students develop their critical thinking skills. Inquisitiveness is one part of the critical thinking disposition that teachers need to have. However, there is still very little research investigating the readiness of prospective teachers in critical thinking dispositions, especially inquisitiveness. This research is intended to determine the level of curiosity of prospective elementary school teachers. This research uses a descriptive qualitative research method, case study type, data, and data sources obtained from 20 prospective elementary school teacher informants in Madiun. Four indicators of inquisitiveness were identified from this case study: Asking questions, seeking information, feeling interested, and final investigation/evaluation. The curiosity of most primary school teacher candidates has not met the four indicators. Few fulfill only one indicator, namely seeking information, and very rarely fulfill three indicators. It can be concluded that prospective elementary school teachers do not yet have the disposition to think critically, especially inquisitiveness. There is a need to improve teacher education learning to improve their students' critical thinking skills and dispositions.